(untitled) (Transport systems and technologies, 2019)
At present, a significant number of units of 1520 mm track calibration wagons in Ukraine have a life span that exceeds that specified by the factory. At the same time, the long-term experience of diagnosing the technical condition of freight and weighing wagons after long-term operation by the specialists of the Scientific and Production Center of Ukrtzaliznytsia branch of JSC Ukrzaliznytsia shows that in most cases the service life specified in the technical conditions is far from the limit. In many ways, this is due both to the substantial safety margin inherent in the design and to the particularities of operating a particular type of wagon. Ensuring safe and timely freight transportation is one of the main tasks of rail transport. In this regard, when at the end of the last century, a shortage of freight rolling stock, including specialized, and taking into account the technical and economic difficulties of its updating after the expiration of the appointed term, it was decided to partially abandon the prescribed scheduled service life for units of rolling stock whose individual resource allowed them to be resolved without further accident-free operation. In recent years, there has been a significant aging of the specialized car fleet. The fleet of weighing wagons has more than 50% of wagons that have served one and a half years or more.